MEDIA FLIPBOOK UNTUK KETERAMPILAN BERBICARA BAHASA JERMAN PESERTA DIDIK SMAN 1 KUTOREJO KELAS XI SEMESTER 2 - FITRIA ASMAATI, WAHYU (LATERNE, 2018)
The background of this research is the lack of supporting media at SMAN 1 Kutorejo Mojokerto for learning speaking skills. This can be seen based on a media analysis filled by German language teachers. The proposed media is Flipbook media. Media Flipbook is a medium created with Corel Draw application. This medium is a series of pictures in a small book that seems to move if the page is turned quickly with thumbs hand. The material used is Mahlzeit and Komparativ Superlativ. The sub theme used is Essen Und Trinken. So problem formulation from this research is How to make Flipbook media for speaking skill of SMAN 1 Kutorejo class XI Semester 2. The purpose of this research is to produce Flipbook as a medium for speaking skill of SMAN 1 Kutorejo class XI second Semester students. The type of this research is development research by using the design theory of development according to Sadiman consisting of (1) identification of needs, (2) formulation of objectives, (3) formulation of material points, (4) formulation of measuring tools of success, (5) draft media and (6) validation. Flipbook media is validated by 2 validators, 1 material validator and 1 media validator. From the results of validation, the percentage is 100% of expert material validators with very good criteria, 83.3% of media validators with very good criteria. So obtained an average of 91.65%. Based on Likert scale Flipbook media is feasible to use in learning. Keywords: Flipbook media, speaking skills, German language